THE ROLE OF HUMAN RESOURCE DEVELOPMENT THROUGH TRAINING AND DEVELOPMENT IN SUPPORTING HOTEL MANAGEMENT (CASE STUDY OF THE GRAND ROYAL HOTEL PANGHEGAR BANDUNG) - Megasari, Cesaria; Fitri Afianti, Azzachra (Akademi Komunitas MAPINDO, 2022)
Development in human resources cannot be separated from standardization for hotels, this is due to the determination of hotel star ratings or hotel standards which will cover three aspects: product, service, and management. In terms of management to ensure service delivery, one of the indicators is human resources. For hotels, this competency will certainly be very important, especially for five-star hotels, the competence itself is basically part of the concept in human resource development efforts. The development of good human resources will also of course go through several strategic steps contained in a business plan. The management and implementation of Banghegar Royal Hotel, especially in the aspect of human resource development, is not smooth, development in human resources is carried out through internal education and training, and employees are sent to group institutions for education that are owned by the hotel. Keywords: HR Development, Management, Hotel Management